Penerapan Media Pembelajaran Audio Visual terhadap Kemampuan Berbicara Siswa Sekolah Darul Muhmin, Thailand: Application of Audio Visual Learning Media on Speaking Ability of Darul Muhmin School Students, Thailand - Putri, Aisyah; Syamsuyurnita, Syamsuyurnita (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Audio-visual-based media learning is one of the learning media that can be seen in pictures and heard directly, commonly called video. This study aimed to describe the application of Indonesian audio-visual (Video) learning media to students' speaking ability at Darul Muhmin School, Thailand. This study uses quantitative data types. This study collects descriptive data from individual behavior consisting of written or spoken words. The subjects of this study were students. This study collected data through observation, interview, and documentation techniques. The study results indicate that the Application of Indonesian Audio Visual (Video) Based Learning Media is good enough to improve the Indonesian Speaking Ability of 6th-grade students at Darul Muhmin School, Thailand. After comparing the previous and post-implementation assessments of Indonesian audio-visual (video) based learning media, it was concluded that the application of Indonesian audio-visual (video) based learning media was considered to have a positive and effective impact on improving the speaking ability of 6th-grade students at Darul Muhmin School, Thailand. The average value obtained at grade 1 was 68.82, and the average at grade 2 was 85.88. This shows an increase in the average value of value 1 to value 2. So, the difference between the average values ??of values one and 2 is 17.06.